Arc-search techniques for interior-point methods - Yang, Yaguang (Boca Raton : CRC Press ; Taylor & Francis Group, 2020)
"This book discusses one of the most recent developments in interior-point methods, the arc-search techniques. Introducing these techniques result in an efficient interior-point algorithm with the lowest polynomial bound, which solves a long-standing issue of the interior-point methods in linear programming, i.e., the algorithm with the best polynomial bound is the least efficient and the most efficient interior-point algorithm cannot be proved to converge. The book also covers important results since 1990s and the extensions of the arc-search techniques to the general optimization problems, such as convex quadratic programming, linear complementarity problem, and semi-definite programming"--
A potential-reduction algorithm for LP -- Feasible path-following algorithms for LP -- Infeasible interior-point method algorithms for LP -- A feasible arc-search algorithm for LP -- A MTY-type infeasible arc-search Algorithm for LP -- A Mehrotra-type infeasible arc-search algorithm for LP -- An O( n̄L) infeasible arc-search algorithm for LP -- An arc-search algorithm for convex quadratic programming -- An arc-search algorithm for QP with box constraints -- An arc-search algorithm for LCP -- An arc-search algorithm for semidefinite programming.
OCLC-licensed vendor bibliographic record.
Keywords: Interior-point methods; Linear programming; Computer algorithms; MATHEMATICS / Applied; MATHEMATICS / Arithmetic; MATHEMATICS / Graphic Methods